L-H transition physics in hydrogen and deuterium: key role of the edge radial electric field and ion heat flux. (20th October 2015) - Ryter, F; Cavedon, M; Happel, T; McDermott, R M; Viezzer, E; Conway, G D; Fischer, R; Kurzan, B; Pütterich, T; Tardini, G; Willensdorfer, M
Abstract: Previous work carried out in the ASDEX Upgrade tokamak on the role of the edge radial electric field and ion heat flux in the L-H transition physics in deuterium plasmas has been extended in hydrogen plasmas. Similar discharges were performed in the two gases providing a detailed comparison of the edge kinetic profiles and heat fluxes in L-mode up to the L-H transition, as the heating power is increased. At the L-H transition, the edge ion heat flux just inside the separatrix is about two times higher in hydrogen than in deuterium. However, the ion plasma parameters at the plasma edge, T i and, as well as the radial electric field well, are found to be very similar in the two gases. The transport analysis based on this data reveals that, at the L-H transition, the ion heat transport at the plasma edge is about two times higher in hydrogen than in deuterium, in agreement with the well-known isotope effect of confinement and transport. This indicates that the higher power threshold in hydrogen is mainly due to the higher ion heat transport in this gas.